Toxoplasma gondii Infection Inhibits Histone Crotonylation to Regulate Immune Response of Porcine Alveolar Macrophages - Yang, Jing; He, Zhengming; Chen, Chengjie; Li, Senyang; Qian, Jiahui; Zhao, Junlong; Fang, Rui (Frontiers in Immunology, 2021)
Toxoplasma gondii (T. gondii) is an obligate intracellular parasite that can infect almost all warm-blooded animals, causing serious public health problems. Lysine crotonylation (Kcr) is a newly discovered posttranslational modification (PTM), which is first identified on histones and has been proved that is relevant to procreation regulation, transcription activation and cell signaling pathway. However, the biological functions of histone crotonylation have not yet been reported in macrophages infected with T. gondii. As a result, a total of 1286 Kcr sites distributed in 414 proteins were identified and quantified, demonstrating the existence of crotonylation in porcine alveolar macrophages. According to our results, identified histones were overall down-regulated. HDAC2, as a histone decrotonylase, was found to be significantly decreased, which might be the executor of histone Kcr after parasite infection. In addition, T. gondii infection inhibited the crotonylation of H2B on K12, contributing on the suppression of epigenetic regulation and NF-κB activation. Nevertheless, the reduction of histone crotonylation induced by parasite infection could promote macrophage proliferation via activating PI3K/Akt signaling pathway. The present findings point to a comprehensive understanding of the biological functions of histone crotonylation in porcine alveolar macrophages, thereby provide a certain research basis for the mechanism research on the immune response of host cells against T. gondii infection.